Puerarin prevents progression of experimental hypoxia-induced pulmonary hypertension via inhibition of autophagy - Xiaodan Zhang; Qi Liu; Chen Zhang; Jiejing Sheng; Songlin Li; Wendi Li; Xinying Yang; Xiaoying Wang; Siyu He; June Bai; Daling Zhu (Elsevier, 2019)
Pulmonary arterial hypertension (PAH) is defined as elevation of mean pulmonary arterial pressure to ≥25 mmHg within the low pressure pulmonary circulatory system. PAH is characterized by obstructive vascular remodeling, partially due to excessive pulmonary arterial smooth muscle cell (PASMC) proliferation. Puerarin is a natural flavonoid isolated from the herb Radix puerariae, which has been widely used for the treatment of cardiovascular and cerebrovascular disorders and diabetes. However, how puerarin mediates autophagy in the progression of pulmonary vascular remodeling is unclear. In this study, we explored the effects of puerarin in a hypoxic pulmonary hypertension (PH) rat model using immunohistochemistry, and morphometric analyses of right ventricle. In addition, cell counting kit 8 assay, western blotting and flow cytometry were employed to test cell proliferation in PASMCs, and then autophagy was tested with mRFP-GFP-LC3 fluorescence microscopy and Western blot. We found that puerarin could alleviate hypoxia-induced PH in rats and improved pulmonary histopathology, and also reduced the expression of autophagy markers in vivo and in vitro. Moreover, puerarin also ameliorated hypoxia-induced PASMC proliferation in an autophagy-dependent manner. Overall, these findings demonstrated that puerarin could prevent hypoxia-induced PH in rats, possibly via reducing autophagy and suppressing cell proliferation. Keywords: Puerarin, Hypoxia, Pulmonary artery hypertension, Autophagy, Proliferation